Ethical Sensitivity, Love of Money, Locus of Control dan Perilaku Etis Mahasiswa Akuntansi - Sanjiwani, Putu Ayu Tasya; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2024)
This study aims to examine the influence of ethical sensitivity, love of money, and locus of control on the ethical behavior of Accounting Students using theory of planned behavior. The population used in this study were all students Bachelor of Accounting Study Program class of 2018 in Udayana University. The sample studied was 154 respondents using a purposive sampling technique. Data was collected through the distribution of questionnaires. The collected data was then processed using multiple linear regression analysis. The results showed that ethical sensitivity, love of money and locus of control has a positive effect on ethical behavior of accounting students. This means that accounting students with high ethical sensitivity, high love of money and high locus of control will show more ethical behavior. Keywords: student ethical behavior; ethical sensitivity; love of money; locus of control